The Influence of Celebrity Endorsement and Brand Love on Purchase Intention - Andri Catur Trissetianto (Greenation Publisher, 2025)
Currently, brand love and celebrity endorsers have become two important elements that influence consumer purchasing choices. The purpose of this study is to examine how brand love and celebrity endorsers influence consumer intentions to make purchases. Through quantitative analysis, data were obtained from a survey conducted on 300 respondents who were active social media users. The results of the analysis show that celebrity endorsements have a positive and significant influence on brand love, which then increases purchase intentions. All of these things support marketers in designing more efficient marketing strategies.